Effective maintenance treatment with lenalidomide for a patient with aggressive adult T cell leukemia after chemotherapy. (2019) - Oka, Satoko; Ono, Kazuo; Nohgawa, Masaharu
Highlights: Relapsed ATL patients who are not eligible for SCT have limited therapeutic options and a poor prognosis. Lenalidomide confers a survival benefit through immunomodulation for patients with relapsed and recurrent ATL. The use of low-dose lenalidomide as maintenance therapy may be a new and promising option for these patients after chemotherapy. Lenalidomide has potential in the treatment of ATL patients, particularly the elderly who are not eligible for SCT. Abstract: Adult T cell leukemia/lymphoma (ATL) is incurable with conventional chemotherapies, and allogeneic stem cell transplantation (SCT) is the only curative treatment. Direct antitumor effects and antitumor immune responses are important factors that need to be considered in the treatment of ATL. A phase II study reported long overall survival despite short progression-free survival in patients, implying that lenalidomide confers a survival benefit through immunomodulation for patients with ATL. We herein report that low-dose lenalidomide as maintenance therapy maintained a complete remission in a patient with aggressive ATL, whose condition has since remained stable with no recurrence for 24 months.